Ultrasonic assisted turning of AISI 52100 steel using nanoparticle-MQL method - Agar, Salih; Tosun, Nihat (Iop Publishing Ltd, 2021)
High cutting force and high cutting tool-chip interface temperature occur during machining of high strength materials like AISI 52100 by using conventional turning method and this makes to the difficult machining operation. Besides, in conventional turning (CT) of these materials, which has high abrasion resistance and hardness properties, an additional process such as grinding is required to achieve the desired surface quality. Ultrasonic assisted turning (UAT) method has been widely used in the machining industry in recent years, as it exhibits better surface quality, lower cutting forces, and cutting temperature than the CT method. This paper focused on experimentally and statistically determining the effects of different cutting parameters and cooling conditions (dry and minimum quantity lubrication-MQL) on surface roughness, workpiece surface texture, tangential direction cutting force, and cutting tool-workpiece interface temperature in the machining of AISI 52100 material by using UAT and CT methods. The experimental results revealed that significant improvements determined in the cutting forces and the surface roughness occurred in UAT compared to CT in all the cooling conditions. However, the increasing cutting speeds caused to observe higher interface temperature values in dry turning by the UAT method. Variance Analysis (ANOVA) was carried out to determine the significance grade of independent variables on dependent variables. According to ANOVA results, while the cutting speed is the most important factor on the surface roughness and the cutting zone temperature, and the cooling method is the most important factor on the cutting force. The effects of turning methods on corresponding surface topography, including surface defects, were evaluated. It is determined that in the surface topography analysis, feed marks are the main texture of the workpiece in the CT method while micro-level indentations and protrusions occurred on the workpiece surface in the UAT method.
Keywords: ultrasonic assisted turning; surface roughness; surface topography analysis; cutting force; tool-chip interface temperature